PREVALENCE OF AUTISM SPECTRUM DISORDER IN SINDH INSTITUTE OF PHYSICAL MEDICINE & REHABILITATION (SIPM&R) - QADEER , MISBAH; Khan, Maroof (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
Autism spectrum disorder (ASD) is a diverse group of conditions, with neurodevelopmental disorders in children and its onset usually starts before three years of age. It is characterized by deficits in communication, social skills along with stereotypical and repetitive behavior. Worldwide autism prevalence has increased dramatically. Same as in Asia frequency of ASD has also raised. The estimated prevalence of ASD in SIPM&R would help the administration to develop strategies and provide training to the therapist. A self-made questionnaire was used to collect the data each day. Sample was taken using simple random sampling method. A total of nine therapists were involved in the study. Sample data were collected from 19th December 2022 to 14th January 2023. Total of 536 patients were seen over period of four weeks. Out of these patients 167 were with ASD. The caseload of solely ASD was 31% at the department. There were 142 males (85%) and 25 females (15%) with ASD. Predominance of male to female ratio was 5:1. The maximum inflow of ASD was from 3-6 years of age. Above seven years only boys with ASD were seen no girls with ASD at the department this month. It is due to stigma and social pressures attached with females that parents don’t expose with the society hence minimum female patients are less reported.